Simple antireflux technique for the cologastric anastomosis: complementary step in retrosternal colon interposition procedure. Issue 8 (1st December 2016) - Abdel-Latif, M.; El-Shafei, E. A.; El-Asmar, K. M.; Abdel-Hay, S.
Summary: Gastrocolic reflux is a troublesome symptom causing repeated aspiration or chocking in patients underwent retrosternal colon interposition. Various techniques were described to avoid such complication, however, they entail complicated technique that may jeopardize the viability of the graft or cause obstructing symptoms. A simple antireflux procedure is described here alleviating this problem. Over the last 7 years, 87 patients had gastrocolic antireflux procedure for cologastric anastomosis; 75 patients as a primary procedure (group 1) and 12 patients as a secondary procedure treating symptomatic reflux (group 2). The technique entails the creation of cologastric angle after finishing the cologastric anastomosis by applying three stitches between the colon and the stomach, thus tucking the colon to the stomach for 3–4 cm. Gastrocolic reflux was evaluated clinically and radiologically 3 months postoperatively. In group 1, three cases (4%) suffered symptomatic gastrocolic reflux, and seven cases (9.3%) had radiological asymptomatic mild reflux, while all patients in group 2 had complete alleviation of their symptoms with gastrogram showing no reflux. Gastrocolic reflux can be treated simply by creation of cologastric angle; however, controlled trial is needed to confirm its effectiveness in comparison to other described techniques.